FOXF2 rs41300825 and NOTCH3 rs1043994 as risk loci for cerebral small vessel disease in Egyptian ischemic stroke patients - Fatma Salama Hussein; Soha Saad Eldin Sayed; Hossam Shokri Mohammed; Maha Moustafa Kamal (Egyptian Journal of Medical Human Genetics)
Abstract Background Cerebral small vessel disease (CSVD) is a significant cause of ischemic stroke in all ethnic groups. Genetic determinants of CSVD are poorly understood and have rarely been explored. One proposed mechanism behind SVD is the breakdown of the blood–brain barrier (BBB). An intact barrier relies heavily on appropriate pericyte (PC) coverage of BBB endothelial cells. FOXF2 and NOTCH3 are two genes implicated in PC development and maintenance, thus influencing PC coverage of brain blood vessels. The aim of this study is to investigate whether FOXF2 rs41300825 and NOTCH3 rs1043994 variants can be considered as candidate loci for CSVD in Egyptian patients, marking the first study of its kind in Egypt. The present study included 186 ischemic stroke patients, selected from neurology and psychiatry department at Ain Shams University hospitals. Patients were categorized into: Group I (SVD patients; n = 114) and Group II (LVD patients; n = 72). Genotyping was conducted for FOXF2 rs41300825 (G/C) and NOTCH3 rs1043994 (A/G/T) using RFLP-PCR, with results confirmed through Sanger sequencing and multiple alignments of sequencing using the MEGA X program. Results Results showed that genotype analysis for FOXF2 rs41300825 displayed one band of 334 bp, indicating the GG genotype. The same was observed for NOTCH3 rs1043994 with one band of 665 bp, representing the GG genotype. Sanger sequencing and multiple alignments of sequencing using the MEGA X program confirmed the results. Conclusion Neither FOXF2 rs41300825 nor NOTCH3 rs1043994 were able to differentiate between patients at risk of developing SVD and those susceptible to LVD. Further studies with larger sample sizes are necessary.